2015
DOI: 10.4103/1305-7456.149670
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background of supernumerary teeth

Abstract: Supernumerary teeth (ST) are odontostomatologic anomaly characterized by as the existence excessive number of teeth in relation to the normal dental formula. This condition is commonly seen with several congenital genetic disorders such as Gardner's syndrome, cleidocranial dysostosis and cleft lip and palate. Less common syndromes that are associated with ST are; Fabry Disease, Ellis-van Creveld syndrome, Nance-Horan syndrome, Rubinstein-Taybi Syndrome and Trico–Rhino–Phalangeal syndrome. ST can be an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 46 publications
(85 reference statements)
2
70
0
15
Order By: Relevance
“…Nance-Horan Syndrome (NHS) (OMIM: 302350) was first described in detail by two independent studies in 1974 as a rare X-linked developmental disorder characterized by congenital cataracts, with occasional dental anomalies, brachymetacarpia and mental retardation [14]. It is inherited as an X-linked recessive trait, whereby heterozygous females manifest a similar but milder disease phenotype than affected males [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nance-Horan Syndrome (NHS) (OMIM: 302350) was first described in detail by two independent studies in 1974 as a rare X-linked developmental disorder characterized by congenital cataracts, with occasional dental anomalies, brachymetacarpia and mental retardation [14]. It is inherited as an X-linked recessive trait, whereby heterozygous females manifest a similar but milder disease phenotype than affected males [5].…”
Section: Introductionmentioning
confidence: 99%
“…Supernumerary teeth (ST) or hyperdontia is one of the most common oral hereditary diseases, characterized with the presence of more than 20 deciduous, or 32 permanent teeth in individuals (Anthonappa, King, & Rabie, ). It occurs from 1.5% to 3.5% in permanent dentition and 0.3% to 0.8% in primary dentition (Garvey, Barry, & Blake, ; Mahabob, Anbuselvan, Kumar, Raja, & Kothari, ) and always follows with other complications such as impacted teeth, malocclusion, and crowded dentition (Subasioglu et al, ), contributing much burden to oral health.…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7] Some studies suggested that the main etiological factor is genetic predisposition related to a disorder associated with a dominant autosomal gene. 2,8 According to other literature, supernumerary teeth are an autosomal recessive feature with incomplete penetrance, or they may be related with the X chromosome. 8 Supernumerary teeth may be related to varied syndromes like Ehlers-Danlos syndrome, Gardner's syndrome, Apert Syndrome, cleidocranial dysplasia and Down's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 According to other literature, supernumerary teeth are an autosomal recessive feature with incomplete penetrance, or they may be related with the X chromosome. 8 Supernumerary teeth may be related to varied syndromes like Ehlers-Danlos syndrome, Gardner's syndrome, Apert Syndrome, cleidocranial dysplasia and Down's syndrome. Supernumerary teeth associated with these syndromes often appear in multiple forms 9 , but they may also occur in patients without such syndromes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation